A rare presentation with synovial osteochondromatosis complicated with septic arthritis: A case report - Boon Tat Yeap; Thai Hau Koo; Xue Bin Leong; Mohd Fauzy Mat Sani; Cu Guan Chua (Proceedings of Singapore Healthcare)
Background Synovial osteochondromatosis is a rare, benign condition characterized by the formation of cartilaginous nodules within the synovium. It commonly occurs in the anterior compartment of the knee joint and predominantly in middle-aged men. It is relatively unusual in females, and at this remarkable age, there is a greater probability of missed diagnosis. Research Design This case report describes a 63-year-old female with classical synovial osteochondromatosis complicated by a clinically suspected septic arthritis of the right knee. Underlying comorbidities, including hypertension, diabetes mellitus, and hyperlipidemia further complicate patient management. Conclusions We have detailed anesthetic and clinical management strategies to stabilize the patient preoperatively and ensure successful surgical outcomes.